Rotating Machineries Aspects of Operation and Maintenance - Sulaiman, Shaharin Anwar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the maintenance aspect of rotating machines, which it addresses through a collection of contributions. Sharing the "hands-on" views of experienced engineers on the aspect of maintenance for rotating machines, it offers a valuable reference guide for practicing engineers in the related industries, providing them a glimpse of some of the most common problems associated with rotating machines and equipment in the field, and helping them achieve maximum performance efficiency and high machine availability.
Condition Monitoring and Assessment for Rotating Machinery -- Turnaround Activities of Rotating Machinery for Mechanical Engineers -- Localization of Gas Turbine Maintenance by Malaysian Gas Turbine Owners and Operators -- Probabilistic Life Cycle Costing: A Case Study of Centrifugal Pumps -- CFD Analysis of Fouling Effects on Aerodynamics Performance of Turbine Blades -- Electrohydrodynamic Pumps for Dielectric Liquid Application -- Experimental Study on Electrical Power Generation from a 1-kW Engine Using Simulated Biogas Fuel.
Keywords: Manufactures; Machinery; Multibody systems; Vibration; Mechanics, Applied; Machines, Tools, Processes; Machinery and Machine Elements; Multibody Systems and Mechanical Vibrations